Unveiling Cultivable and Uncultivable Halophilic Bacteria Inhabiting Marakkanam Saltpan, India and Their Potential for Biotechnological Applications. Issue 8 (13th July 2020) - John, Jojy; Siva, Vinu; Kumari, Richa; Arya, Aditya; Kumar, Amit
Abstract: The present study aims to characterize cultivable and uncultivable halophilic bacteria inhabiting Marakkanam saltpan located in south India. In addition, cultured bacteria were screened for enzymes of industrial importance, heavy metal tolerance, and ability to grow in crude oil as well as antagonistic activity against shrimp pathogen Vibrio parahaemolyticus . Uncultivable bacteria using MinION sequencing showed the presence of eight bacterial phyla belonging to fifty-five genera with an abundance of class Betaproteobacteria (59%). A total of eight bacterial strains were isolated, identified and phylogenetically characterized using 16S rRNA gene sequence. Out of eight, five isolates showed resemblance to the genus Chromohalobacter ( Gammaproteobacteria ), two to the genus Halovibrio ( Gammaproteobacteria ), and one to the genus Staphylococcus ( Firmictues ). All of the isolated strains were capable of producing lipase and protease, tolerant to heavy metals like cobalt, lead, arsenic zinc, copper, chromium, and mercury but sensitive to silver. Two strains of Chromohalobacter were capable to grow in crude oil indicating their potential for hydrocarbon degradation. Four strains were detected to have antagonistic activity against V. parahaemolytics . This study indicated presence of wide varieties of halophilic bacteria detected by next generation sequencing method in the previously unexplored saltpan. In addition, all the cultivable bacteria showed great potential as a source for different biotechnological applications.